Impact of Postgraduate Student Internships During the COVID-19 Pandemic in China - Zhang, Wenyi; Lu, Xiaozhong; Kang, Derong; Quan, Jiaxin (Frontiers in Psychology, 2022)
To understand the impact of the COVID-19 pandemic on postgraduate students’ internships in China, 911 students from different regions of China were interviewed through online questionnaires, self-developed questionnaires, anxiety self-assessments, and depression self-assessments. Among the postgraduate students surveyed, 47.53% and 59.60% believed that the pandemic had its greatest impact on their colleague interactions and their practical skills. In total, 31.8% of postgraduate internship programs were impacted by COVID-19. The proportions of respondents having severe, moderate, and mild anxiety levels were 1.42%, 4.72%, and 15.92%, respectively, and the rates of major, moderate, and mild depression were 1.64%, 10.86%, and 21.84%, respectively. A one-way ANOVA found that professional background, degree type, and degree of impact of the pandemic on colleague interactions and improved practical abilities all affected postgraduate mental health. The findings suggest that the mental health of postgraduate students should be monitored during an pandemic, focusing on their anxiety and depression, and targeted psychological counseling should be offered. Postgraduate internships during an pandemic period should be developed, ensuring a smooth internship process, as much as possible, and providing training to postgraduate students. To help postgraduate students adapt to the new internship and employment conditions brought on by the new normal of pandemic prevention and control, corresponding psychological counseling and assistance should be provided.